Breakdown and discharge in low pressure gas created by a microwave radiation undergoing stochastic phase jumps (II) - Karas`, V.I.; Alisov, A.F.; Artamoshkin, A.M.; Bingham, R.; Gavrilenko, I.V.; Zagorodny, A.G.; Zagrebel`ny, I.A.; Lontano, M.; Mirny, V.I.; Potapenko, I.F.; Us, V.S. (Вопросы атомной науки и техники, 2006)
The objective of the paper is to discuss the results of theoretical and experimental studies and numerical simulations
of following phenomena: the anomalous character of the breakdown conditions, the anomalous behavior of microwave
gas discharges, and the anomalous nature of collisionless electron heating that are attributed to stochastic jumps in the
phase of microwave radiation.